Design of an efficient flake powder metallurgy route to fabricate CNT/6061Al composites. (15th March 2018) - Chen, Malin; Fan, Genlian; Tan, Zhanqiu; Xiong, Dingbang; Guo, Qiang; Su, Yishi; Zhang, Jie; Li, Zhiqiang; Naito, Makio; Zhang, Di
Highlights: CNTs can be de-agglomerated and uniformly coated onto surface of Al powder via the mechanism of dry particle coating; High-shear pre-dispersion process promoted the dispersion efficiency, uniformity and structural integrity of CNTs; Simultaneous enhancement in tensile strength, Young's modulus and ductility were achieved in the pre-dispersed composite. Graphical abstract: Unlabelled Image Abstract: A flake powder metallurgy route that combines high-shear pre-dispersion process with shift-speed ball milling was designed to fabricate carbon nanotube reinforced aluminum composites. In order to mitigate the dispersion responsibility of ball milling and improve the dispersion efficiency, high-shear pre-dispersion process utilizing the mechanism of dry particle coating was firstly applied to CNTs and 6061Al powder mixtures for a few minutes to de-agglomerate CNTs and uniformly coat them onto surface of 6061Al powder. It was demonstrated that, for the pre-dispersed powders, more rapid and uniform dispersion of CNTs was achieved during following shift-speed ball milling process, which in turn protected CNTs from additional damage and led to better interfacial bonding and higher reinforcing efficiency. As results, compared to counterpart without pre-dispersion, the as-extruded bulk 1.5 wt% CNT/6061Al composites exhibited simultaneous enhancement in Young's modulus, tensile strength and ductility.